Form and Deformation, the Expression and Expressionism - Aumont, Jacques (Iluminace, 2003)
A study and analysis of the relationship between cinema and painting with a focus on expressionism.
Keywords: film aesthetics; painting and film; film theory; expressionism (art) and film; expressionism (film)